Metallocorroles for Attenuation of Atherosclerosis - Haber, Adi.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Adi Haber's thesis summarises the use of a new entity, the corrole, to combat one of the major cardiovascular diseases, atherosclerosis. She examines the effects of three rationally designed corrole-metal complexes on some of the many variables which contribute to the development of atherosclerosis. There is a focus on both the "bad" and "good" cholesterol carriers, LDL and HDL. Adi Haber proceeds from basic findings in pure chemistry through biochemical and cell culture tests to in vivo examinations. The work in this thesis shows that corroles are highly efficient both for early and late treatment of atherosclerosis in animals. These results will pave the way for ongoing regulated preclinical studies focussed on the development of metallocorroles as potential drugs for treating cardiovascular diseases.
Biologically relevant ROS/RNS -- Atherosclerosis -- The pro-atherogenic role of LDL and macrophages -- The anti-atheroginicity of HDL -- Common treatments for atherosclerosis -- Corroles -- Catalytic antioxidants -- Electronic spectra -- Research Goals -- Results -- Interactions of corroles with lipoproteins -- Corrole-lipoproteins binding -- Corrole distribution in serum -- Spectral changes in the presence of lipoprotein components -- The effect of corroles on oxidative-stress-induced lipoprotein damage -- Cu+2-induced oxidation -- Peroxynitrite-induced oxidation -- Lipoprotein function -- Interactions of corroles with macrophages -- Fluorescence-based detection of 1-Ga -- Chemiluminescence-based detection of 1-Fe -- Cellular accumulation of 1-Fe versus iron(III) porphyrins -- The effect of corroles on macrophage atherogenicity -- Effect on oxidative-stress-induced cell death -- Effect on macrophages cholesterol metabolism.-The effect of corroles on the development of atherosclerosis -- Discussion -- Interaction of corroles with lipoproteins -- Corrole distribution in serum -- Mode of 1-Fe binding to lipoproteins -- Materials and Methods.
Keywords: Chemistry; Organometallic chemistry; Biochemistry; Chemistry; Organometallic Chemistry; Biochemistry, general; Biomedicine general; Electronic books